Flower Image Retrieval Using Color and Shape Features and Multiple Distance Functions - Bulbul, Mohammad Farhad; Happy, Khadiza Sultana; Azme, Zannatul (European Journal of Applied Sciences, 2019)
It is noticeable that when flower images are observed, flower’s color signifies people and often people ignore small and isolated sectors of the image. So for retrieving flower images color feature of the images is very important. Different flowers have also different shapes. So for differing flower images from another flower images shape feature is also a significant feature. In this paper, we proposed a method of retrieving flower images using their color and shape feature. We used HSV color histogram, color moments and color auto correlogram descriptors for describing color feature and HOG descriptor for describing shape feature. We calculate the similarities between the query image and the database images by employing a set of distance functions. We evaluated our result for our own dataset of 15 categories flower images.